REVIEW: PERKEMBANGAN LITERASI DAN INKLUSI KEUANGAN PASAR MODAL DI NUSA TENGGARA BARAT (NTB) - Nurul Susianti1, Kurniawati Meylianingr2 Fitriani,Siti Nur Annisa Amalia (UIN Mataram, 2019)
AbstractThis study focuses on the problem of reviewing the development of financial literacyand inclusion in the field of capital markets, especially investment funds, and mutualfund and SBN in 2017-2018. This study uses descriptive analysis that distributesdescribing the results of documentation interviews and observations in severalinstitutions in West Nusa Tenggara, especially the Indonesia Stock ExchangeRepresentative Office and the Financial Services Authority. This study shows thatliteracy in the capital market in West Nusa Tenggara is quite positive, especially in thefield of stock investment with a value of 10. 22%.